PERFORMA BROILER STRAIN CP 707 DAN STRAIN MANGGIS (AM 888) YANG DIPELIHARA PADA KANDANG POSTAL DOUBLE DECK SISTEM SEMI-CLOSE HOUSE: PERFORMANCE OF BROILER STRAIN CP 707 AND MANGOSTEEN STRAIN (AM 888) MAINTAINED IN POSTAL DOUBLE DECK CAGES OF SEMI-CLOSE HOUSE SYSTEM - Umaternate, Siti N; Horhoruw, Wiesje M.; wattiheluw, juraid (Universitas Djuanda, 2023)
Broiler strains are breeding results produced by breeding farms for certain economical purposes. Each type of broiler strain certainly has different advantages, so it will have an impact on the resulting performance. This study aims to determine the performance of broiler strain CP 707 and mangosteen strain (AM 888) which are kept in postal double deck cages with a semi-close house system. The materials in this study are broiler strain CP 707 and mangosteen strain (AM 888) which are raised in postal double deck cages with a semi-close house system, a population of 22,000 heads / cage and commercial feed types SB 8108 and TOP 8118 P. This research was carried out for 21 days on the broiler farm of Mr. Rahmatullah Rosidin Galih B and C with a double deck postal cage type in Kidin Village, Kibin District, Serang Regency, Banten. The method used in this study is survey and observation (direct observation in the field) to retrieve data related to broiler performance. The variables observed in this study were feed intake, weight gain, feed conversion ratio (FCR) and depletion. The data obtained are analyzed descriptively. The results showed that the performance of broiler strain CP 707 was better than the mangosteen strain (AM 888). This is because broilers of the CP 707 strain are obtained the amount of feed intake, higher body weight gain, as well as a lower feed conversion ratio (FCR) and depletion rate compared to broilers of the mangosteen strain (AM 888).